Case Report: Sympathetic nerve block treat chronic kidney disease-associated pruritus - Li, Ying; Chen, Yaohua; Nie, Jingyi; Huang, Xiaoguang; Zhang, Weiwei (Frontiers in Neuroscience, 2025)
Uremia is the advanced stage of chronic kidney disease (CKD), characterized by the accumulation of metabolic waste products in the blood as a result of the kidneys' inability to meet the body's metabolic demands. Patients with uremia frequently experience a range of complications, including renal anemia, osteoporosis, and cardiovascular disease, all of which significantly impair their quality of life. Chronic kidney disease-associated pruritus (CKD-aP) is a common comorbidity in uremic patients, particularly among those undergoing hemodialysis, with prevalence rates ranging from 10 to 77%. This case report enrolled three patients diagnosed with chronic kidney disease-associated pruritus (CKD-ap) who underwent ultrasound-guided sympathetic nerve blockade procedures. The results demonstrated significant reductions in pruritus intensity concurrent with measurable enhancements in sleep quality and daily functioning.